“BENTUK HORMAT” DIALEK BAHASA BALI AGA DALAM KONTEKS AGAMA - Hara Mayuko (Masyarakat Linguistik Indonesia, 2015)
Balinese language has two major dialects, Lowland Balinese dialect (BD dialect) and Mountain Balinese dialect (BA dialect). BD dialect has a systematic form of respect (Sor Singgih Basa, Unda Usuk Basa) which is based, mainly, on the differences of caste between speakers in the society. In the BA community, however, there is no difference of social status groupings. Thus, in principle BA dialect does not have the system and use of honorifics. However, speeches at prayers contain the honorific words which are the same as or similar to Kruna Alus, Kruna Alus Singgih, Kruna Alus Sor of BD dialect. This paper describes the “honorifics” of BA dialect used in the Pedawa village based on analysis of speeches at prayers, and points the possibility of interference and borrowing from BD dialect to BA dialect through religious domain.